2018
DOI: 10.1051/0004-6361/201731125
|View full text |Cite
|
Sign up to set email alerts
|

The quest for stable circumbinary companions to post-common envelope sdB eclipsing binaries

Abstract: Context. Period variations have been detected in a number of eclipsing close compact binary subdwarf B stars (sdBs) and these have often been interpreted as caused by circumbinary massive planets or brown dwarfs. According to canonical binary models, the majority of sdB systems are produced from low mass stars with degenerate cores where helium is ignited in flashes. Various evolutionary scenarios have been proposed for these stars, but a definite mechanism remains to be established. Equally puzzling is the fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
4
11
0
Order By: Relevance
“…The only possibility for our technique missing this planet would be an orbital inclination lower than 43 • . Our conclusion supplements the work by Pulley et al (2018) based on recent observations of seven sdB systems. The authors show that period variations of these stars cannot be explained simply on the basis of third bodies orbiting these systems.…”
Section: Discussionsupporting
confidence: 90%
“…The only possibility for our technique missing this planet would be an orbital inclination lower than 43 • . Our conclusion supplements the work by Pulley et al (2018) based on recent observations of seven sdB systems. The authors show that period variations of these stars cannot be explained simply on the basis of third bodies orbiting these systems.…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that these findings are in agreement with the so-called Applegate mechanism, which proposes that variability in the binary orbits can be driven by magnetic cycles in the secondary stars. In all published HW Vir systems with a longer observational baseline of several years quite large period variations on the order of minutes have been detected (see Zorotovic & Schreiber 2013;Pulley et al 2018, for an overview), with the exception of AA Dor (Kilkenny 2014), which still shows no sign of period variations after a baseline of about 40 years. Also the orbital period decrease in J08205+0008 is on the order of seconds and has only been found after 10 years of observation and no additional sinusoidal signals have been found as seen in many of the other systems.…”
Section: Orbital Period Variations In Hw Vir Systemsmentioning
confidence: 99%
“…Pulley et al (2015) showed that the more recent O-C timing data began to diverge from the Qian model. Later in 2018, they confirmed this departure by adding 65 more times of minima (Pulley et al 2018). Bogensberger et al (2017) proposed a new one planet model with a longer orbital 11.8 year period, eccentricity 0.38, and no quadratic term.…”
Section: Hw Virginismentioning
confidence: 94%
“…Almeida et al (2017) reported eight more eclipse times and updated the linear ephemeris. Most recently, Pulley et al (2018) extended the timing database with 26 more timing minima. They compared the quadratic ephemeris by Qian et al (2010) and linear ephemeris proposed by Lohr et al (2014) concluded there is no statistically significant difference between the two.…”
Section: Hs2231+2441mentioning
confidence: 99%
See 1 more Smart Citation